The Correlation between Hyperuricemia and Cardiovascular Morbidities among Hemodialysis Patients Attending the Academy Charity Teaching Hospital From Jan 2019 - Dec 2019 - Abushunnar, Mohammed Walid Khalil (Cardiology and Cardiovascular Medicine, 2022)
Objectives: To determine The prevalence of hyperuricemia and the association between uric acid level and various cardiovascular morbidities in patients with ESRF whom undergoing regular hemodialysis sessions. Methods: Descriptive retrospective facility based study included all hemodialysis patients who attended the hemodialysis unit at the Academy Charity Teaching Hospital from January 2019 – December 2019 which was equivalent to 150 patients, Data collected from patient’s files using data collection sheet then entered in Microsoft-excel and analyzed statistically using SPSS. Results: the study population included 150 patients, Male to female ratio 3:2, with a mean age of 54 years ±17. (21.3%) of the study participants live in Jabra region, 57% were jobless (30% were unemployed and 27% were housewives). CKD represented 89,59% of the etiological factors of ESRF. The median time spent by patients since the start of dialysis is 36 months. The overall prevalence of hyperuricemia was 62% and The most frequently associated comorbid condition was hypertension with 99% followed by Myocardial Infarction with 12.7% of patients. 44% of participants were taking Allopurinol plus CaCo3 and 18% were CaCo3 alone. the association between the serum uric acid levels and myocardial infarction was proven to be statistically significant with p value of 0.037. On the other hand, association between hyperuricemia and stroke, heart failure was found to be statistically insignificant. Conclusion: prevalence of hyperuricemia is high in patients with ESRD whom undergoing regular hemodialysis sessions and Serum uric acid is significantly associated with myocardial infarction. Hyperuricemia should be acknowledged and monitored as a risk factor for cardiovascular disease.<